Pengaruh Permainan Alphabet Fishing Terhadap Kemampuan Mengenal Huruf Anak Kelompok A di TK Permata Sunnah Kecamatan Kota Selatan Kota Gorontalo - Rizky Mahrianty Husain; Yakob Napu; Rapi Us Djuko (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2024)
This study aims to determine the effect of the Alphabet Fishing game on the letter recognition ability of children in group A. This research is quantitative with an experimental method and uses a pre-test and post-test research design involving tests administered before and after the intervention. The study subjects consisted of 15 children in group A at TK Permata Sunnah Kindergarten, Gorontalo City. The object of this research was to improve the letter recognition ability of group A children through the Alphabet Fishing game. Data collection for one group pretest posttest design was carried out using research instruments. Data analysis was conducted using statistical data processing techniques. The results showed a significant difference in children's average letter recognition ability before and after the intervention, as evidenced by the pre-test and post-test scores of 13.8 and 26.8, respectively. These results demonstrated a significant effect of the intervention. Based on the t-test results, the significance test yielded tcount of 17.00, while the ttable value (α = 0.05) is 2.131. Since tcount > ttabel ; 17,00 > 2,131, H0 was rejected, and H1 was accepted. This indicated that the Alphabet Fishing game significantly affects the letter recognition ability of group A children at TK Permata Sunnah Kindergarten. In conclusion, there is a significant difference in group A children's ability to recognize letters in the pre-test and post-test data. Thus, variable x has an effect on variable y.